Psychotherapy and Counseling with Older Women : Cross-Cultural, Family, and End-of-Life Issues. - Trotman, Frances (Springer series, focus on women., 2001)
Trotman and Brody, along with expert contributors, view older women through a feminist lens and examine social constructs concerning aspects of aging, caregiving, elders' relationships with family, health, body image, and sexuality concerns. The authors define issues that are important to older women and their emotional health and bring into sharp relief some of the painful issues professionals must confront in counseling older women.